Peran Pertumbuhan Ekonomi Dalam Hubungan Antara Pengeluaran Pemerintah dan Investasi Terhadap Pendapatan Asli Daerah (Studi Empiris pada Pemerintah Kabupaten/Kota di Jawa Tengah) - Astriyani, Lilis; , Dr. Zulfikar, SE, MSi (2016)
This research aim to know direct influence of government spending and investment to local genuine revenues and direct influence of government spending and investment to growth of economics and also influence of growth of economics to local genuine revenues and indirect influence of government spending and investment to local genuine revenues Regency/Municipality in the Province of Central Java. This research use quantitative method by using report data realizes revenue plan and local expense (APBD) and also the tables of domestic product regional of gross (PDRB) Regency/Municipality in the Province of Central Java. Population and sample used at this research are Regency/Municipality in the Province of Central Java amounting to 35 Regency/Municipality spanned time of year 2013-2015. The data analyses used include test of normality, test multicolinearity, test heteroskidastity, path analysis, test of F, test of t, and coefficient of determinacy (Adjusted R2). Pursuant to result of data analyses can be concluded that government spending and investment have an effect on positive and direct to local genuine revenues. Government spending have an effect on positive and direct to growth of economics, while investment do not have an effect on positive and direct to growth of economics. Growth of economics has an effect on positive and direct to local genuine revenues. Government spending and investment to through mediation of growth of economics have an effect on positive indirectly to local genuine revenues. Test of F indicate that government spending, investment and growth of economics have an effect on by together (simultaneous) to local genuine revenues. Coefficient of determinacy test of Adjusted R2 showing the local genuine revenues influenced by government spending, investment and growth of economics equal to 43,4%, and the model have got away from result of classical assumption. Keyword: Growth of Economics, Government Spending, Investment, Local Genuine Revenues.